Investigation of palladium nanoparticles supported on metallic titanium pillars as a novel electrode for hydrogen peroxide electroreduction in acidic medium. (1st October 2017) - Song, Congying; Li, Biaopeng; Ye, Ke; Zhu, Kai; Cao, Dianxue; Cheng, Kui; Wang, Guiling; Pan, Yue
Graphical abstract: Highlights: Pd@Ti Ps reveal higher catalytic activity than Pd@Ti plate. Pd@Ti Ps show unique 3D structure with a large surface area. Pd@Ti Ps exhibit good stability for H2 O2 electroreduction in acidic medium Abstract: An especial current collector of Ti pillar arrays (Ti Ps) is prepared by a facile hydrothermal etching method. The Ti Ps substrate can be applied in acidic medium for its excellent stability, and the large specific surface area of this substrate is highly beneficial to the contact between electrolyte and catalyst. Pd deposited on the Ti Ps substrate is selected to be the catalyst for H2 O2 reduction due to its remarkable electrocatalytic activity and stability. The structure and phase composition of the Pd modified Ti Ps (Pd@Ti Ps) electrode are studied through X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and inductive coupled plasma emission spectrometer (ICP). The electrocatalytic property of the Pd@Ti Ps electrode is studied through cyclic voltammetry (CV) and chronoamperometry (CA). According to the results, the Pd@Ti Ps electrode exhibits a high reduction current density of 220 mA cm −2 at −0.2 V in 2 mol L −1 H2 SO4 and 0.5 mol L −1 H2 O2 which is greatly larger than that on Pd modified Ti plate (Pd@Ti plate) electrode. The activation energy of H2 O2 reduction on this electrode is 19.77 kJ mol −1 . The low activation energy and high electrocatalytic activity indicate that the as-prepared electrode can be applied as a potential cathode for fuel cell.